The psychometric properties of the Persian version of midwives' knowledge and skills questionnaire to assess and promote maternal health literacy - Bita jamali; Hamid Sharif-Nia; Omolbanin Zare; Majedeh Nabavian (Mashhad University of Medical Sciences, 2023)
Introduction: The knowledge and skills of midwives as the most effective team providing health and preventive care can affect the behavior and performance of maternal care. Therefore, the present study was conducted with aim to examine the psychometric properties of the Persian version of midwives' knowledge and skills questionnaire to assess and promote maternal health literacy. Methods: This methodological and cross-sectional study was conducted from November 2022to February 2023. In this study, 314 midwives working in hospitals and health centers or public and private clinics in the central cities of Mazandaran province completed the 13-item questionnaire. The face validity, content validity and construct validity of the questionnaire was evaluated. The reliability was obtained using Cronbach's alpha and test-retest reproducibility. The structure of the questionnaire was analyzed using factor analysis. Results: Based on the results of exploratory factor analysis, three factors of performance, knowledge and skills were extracted. The model fitness indices confirmed the questionnaire. (PCFI=0.684, PNFI=0.651, CMIN/DF=2.438, RMSEA=0.068, AGFI=0.905, IFI=0.923, CFI=0.922). Also, the internal consistency and reliability of the questionnaire were confirmed (<0.7). Conclusion: The three-factor questionnaire of midwives' knowledge and skills to assess and promote maternal health literacy produced good validity and reliability. Due to its suitable psychometric properties, this tool can be used in future studies designed to evaluate midwives' knowledge and skills to assess and promote maternal health literacy.